Answer:
-t*(t -16) ≥ 39
-t*(t -16) = 39
t = 3 or 13 hours
Explanation:
When number of people is at 39 or more means the number of people of greater than or equal to 39.
So, the inequality is,
-t*(t -16) ≥ 39
When the number of people is 39, the equation is,
-t*(t - 16) = 39
-t²+ 16t = 39
0 = 39 + t² - 16t
t² - 16t + 39 = 0
Sum = -16
Product = 39
Factors = -3 , -13 [ (-3) * (-13) = 39 & (-3) +(-13) = -16 ]
Rewrite the middle term using the factors.
t² - 3t - 13t + 39 = 0
t(t -3) - 13(t - 3) = 0
(t -3)( t - 13) = 0
t -3 = 0 ; t- 13 = 0
t = 3 or t = 13
t = 3 hours or 13 hours.